PENERAPAN SENSOR SHT 11 TERKENDALI MIKROKONTROLER SEBAGAI PENGKONDISI SUHU DAN HUMIDITAS RUMAH WALET - Kristiyana, Samuel (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2010)
The Walet bird`s nests are believed to have some healing power for a number of diseases. Therefore, they are highly valued commercially, so that the drive to collect them are very strong from hazardous places such as caves,cliffs, steep shoves, dense forests, etc. Efforts to give artificial homes for the Walet birds are promising for business, espe-cially for the much lower workers safety risks and more stable best`s quantity produced. Some challenges have to be able to overcome resorting to the regulating power of a mi-crocontroller. First of all, to atract the birds, the design of would be home should be stu-died thoroughly, including its location away from the disturbing human activities. Second, the right indoor atmosphere condition should be guaranteed. A set of hardware can be developed to provide a monitoring system on the temperature, humidity as well as the illumination level of the room dedicated for the Walet. To maintain the right temperature and humidity, an automatic water sprayer unit is added during the dry days of the year. A programmable Walet sound reproducing equipment is vital to safe the farmer`s time to operate it manually.